Порівняльний аналіз середньовічної візантійської ( орієнтально-православної ) та окцидедентально-католицької традицій в політико-правовій владі західноєвропейських держав - Дунаєва, Л. М.; Дунаева, Л. М.; Dunaeva, L. (My University, 2010)
In the article the basic approaches to analysis of conceptions of power in political-law idea of the Western-European countries are examined. They based on ancient legacy and to Roman school of right. Then they formed different directions in understanding of optimum correlation of society and church power owing to change of historical and religious-cultural terms.
Дунаєва Л. М. Порівняльний аналіз середньовічної візантійської ( орієнтально-православної ) та окцидентально-католицької традицій в політико-правовій владі західноєвропейських держав / Л. М. Дунаєва // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 26-36.
Keywords: церква в політико-правовій теорії влади західноєвропейських держав; середньовічна візантійська ( орієнтально-православна ) традиція у політико-правовій владі західноєвропейських держав; окцидентально-католицька традиція в політико-правовій теорії влади західноєвропейських держав; римська школа права; співвідношення церковної і світської влади у західноєвропейських державах; церковь в политико-правовой теории власти западноевропейских стран; средневековая византийская ( ориентально-православная ) традиция в политико-правовой власти западноевропейских стран; окцидентально-католическая традиция в политико-правовой теории власти западноевропейских государств; соотношение светской и церковной власти в западноевропейских странах; римская школа права; Church in political and legal theory of power of Western European countries; Medieval Byzantine (oriental-orthodox) tradition in political and legal power of Western European countries; oktsidentalno Catholic tradition in political and legal theory of the power of Western European states; the ratio of the secular and ecclesiastical authority in Western European countries; Roman Law School